Strategi Media Branding Pengembangan Sektor Pariwisata Kabupaten Pesisir Barat sebagai Destinasi Wisata Internasional - Okta Vianti; Dian Kagungan; Devi Yulianti (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
The phenomenon that occurs in modern society is starting tourism activities so that there must be a strategy that is in accordance with the times and can be used as management and development of tourism potential by utilizing digital media as a media for branding which is part of marketing communication. The purpose of this study is to determine the implementation of media branding strategies in the development of the tourism sector in Pesisir Barat Regency as an international tourist destination, supporting and inhibiting factors that affect media branding in the development of the tourism sector, as well as the impact of the Covid-19 pandemic on the tourism sector in Pesisir Barat Regency. This type of research is a descriptive study with a qualitative approach. The results showed that the implementation of the media branding strategy for the development of the tourism sector in Pesisir Barat Regency as an international tourist destination, namely the setting of annual goals, its implementation is still minimal because it is not well directed as well as the use of less massive media in an effort to branding tourism; policy formulation, namely the existence of a decree on the division of tourism villages; motivating workers with the efforts that have been made such as mutual encouragement, coordination, and evaluation in private meetings or invitations; lack of allocation of qualified human resources in the IT field. Furthermore, the supporting and inhibiting factors that influence the branding media are the role of the community which indirectly participates in branding the existing tourism potential as well as the limited quality and quantity of human resources and the lack of the role of the government. Then the impact of the Covid-19 pandemic resulted in a decrease in the number of tourists and the cancellation of events that had been prepared